Calculation of Alr-Distribution while Storing Agricultural Products in Temporary Works - P. I. Dziachek (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2006)
Using calculus techniques of solving filter equations the investigation has been carried out to find air distribution in cross-section area of storing bunkers and trenches. The engineering procedure has been suggested to estimate processes of air flow in temporary works for storing agricultural products and a method for calculating aerodynamic resistance in layers of stored products has been developed. At the design stage the presented information allows to choose an efficient ventilating system and the required type of a storing bunker.